Michael Wolff über Beweise für vollkommene Syllogismen bei Aristoteles. - Ebert, Theodor (Journal for General Philosophy of Science, 2010)
The paper rejects Michael Wolff's claim that Aristotle offers proofs for the validity of his perfect syllogisms.
Keywords: perfect syllogism